2020
DOI: 10.1021/acs.jpclett.0c02037
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Induced Adsorption and Structuring of Water at the Pt(111) Electrode Surface in Contact with an Ionic Liquid

Abstract: Water adsorption is important in many fields from surface electrochemistry to electrocatalysis, where molecular-level information is much needed in order to gain a detailed understanding of the role of interfacial water. Here we report on water at Pt(111) surfaces in contact with an [EIMIM]­[BF4] ionic liquid, which was spectroscopically resolved by using in situ sum-frequency generation (SFG). O–H modes are used to study water adsorption and water structure as a function of electrode potential, while the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Clearly, the choice of the anion, e.g., NTf 2 in this work as opposed to [BF 4 ] or [DCA] in previous works, , has also a major effect on the CO formation from CO 2 RR and can lead to substantially different CO coverages at moderately low cathodic potentials of −0.4 to −0.7 V. This can be related to the strong anion–water interaction that plays a key role in the water accumulation at the interface . Kobayashi et al demonstrated that for ILs with a high packing fraction and hydrophilicity, the infusion of water in the interfacial layer can be entropically favored, which was confirmed by in situ vibrational SFG spectroscopy of the Pt(111)/[EMIM]­[BF 4 ] interface, where the co-adsorption of water at the interface leads to an extended and hydrogen-bonded interfacial layer of water molecules . Clearly, the active C2 position at the imidazolium ring as discussed in the Introduction section is not the only factor that can lower the overpotential for CO formation as well as the onset for other CO 2 RR.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Clearly, the choice of the anion, e.g., NTf 2 in this work as opposed to [BF 4 ] or [DCA] in previous works, , has also a major effect on the CO formation from CO 2 RR and can lead to substantially different CO coverages at moderately low cathodic potentials of −0.4 to −0.7 V. This can be related to the strong anion–water interaction that plays a key role in the water accumulation at the interface . Kobayashi et al demonstrated that for ILs with a high packing fraction and hydrophilicity, the infusion of water in the interfacial layer can be entropically favored, which was confirmed by in situ vibrational SFG spectroscopy of the Pt(111)/[EMIM]­[BF 4 ] interface, where the co-adsorption of water at the interface leads to an extended and hydrogen-bonded interfacial layer of water molecules . Clearly, the active C2 position at the imidazolium ring as discussed in the Introduction section is not the only factor that can lower the overpotential for CO formation as well as the onset for other CO 2 RR.…”
Section: Resultsmentioning
confidence: 80%
“…42 Kobayashi et al 43 demonstrated that for ILs with a high packing fraction and hydrophilicity, the infusion of water in the interfacial layer can be entropically favored, which was confirmed by in situ vibrational SFG spectroscopy of the Pt(111)/[EMIM][BF 4 ] interface, where the co-adsorption of water at the interface leads to an extended and hydrogen-bonded interfacial layer of water molecules. 44 Clearly, the active C2 position at the imidazolium ring as discussed in the Introduction section is In Figure 4a, we focus on the FT-IRAS spectra of Pt electrodes in a CO 2 -saturated [BMIM][NTf 2 ] electrolyte that contained 0.5 M H 2 O. After reaching −0.45 V during the cathodic potential sweep, a vibrational band in the carbonyl stretching region starts to rise at 1672 cm −1 and is accompanied by an absorption loss at 2343 cm −1 that can be attributed to a consumption of CO 2 due to ongoing CO 2 RR.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…SFG investigations of water in [C 2 mim][BF 4 ] at a Pt(111) surface revealed that the electrode potential causes free water molecules from the bulk to form a network of hydrogen-bonded water molecules at the interface (see Figure 2). 34 By using water electrosorption as a "reporter molecule", the authors determined the potential of zero charge (PZC) of Pt in the IL to be +0.1 V versus a standard hydrogen electrode (SHE). These diverse studies reveal the complicated behavior of water at the EDL in ILs, presumably caused by strong bonding interactions with the ions.…”
Section: Introduction−structure Of the Electricalmentioning
confidence: 99%
“…In many ionic liquids, it has been found that water leads to distortion and weakening of the interface structure [ 27 , 28 ]. This has been attributed to the preferential adsorption of water on the electrified electrode, as well as to the interaction between the H 2 O molecules and ions of the PIL via hydrogen bonds [ 29 ]. However, in some ionic liquids, the presence of water was found to be a prerequisite for the formation of a detectable structured interface layer [ 30 ].…”
Section: Introductionmentioning
confidence: 99%